Nursing of a lung cancer patient with insomnia treated with five-element energy cupping therapy (1例肺癌伴失眠患者行五行能量罐疗法的护理体会) - YAN Kang (严康); LIU Shuhong (刘书红); ZHAO Yanan (赵亚楠) (中西医结合护理)
This paper reviewed the clinical effect of five-element energy cupping therapy in the treatment of heart-spleen deficiency type insomnia in a lung cancer patient, and summarized related nursing measures. Based on the conventional nursing interventions on daily life support, dietary, exercise and mental health, the five-element energy cupping therapy by Traditional Chinese Medicine syndrome differentiation was carried out to relieve the insomnia and improve the sleep quality of the patient. (本文总结五行能量罐疗法干预1例心脾两虚型肺癌伴失眠患者的效果及护理经验。患者入院后, 医护人员做好起居、饮食、运动以及情志干预等常规护理, 基于中医辨证, 采用五行能量罐疗, 有效缓解失眠症状, 提高睡眠质量。)